Scot free : the lighter side of the dark underbelly of the California dream - McPherson, Catriona, 1965- (McPherson, Catriona, 1965- Last Ditch mystery, 2018)
Lexy Campbell fell in love and left her native Scotland for a golden life in California--hitched to a hunk, building her marriage counseling practice, living the dream. Six months later she's divorced, broke, and headed home. There's just one last thing. Lexy's only client--sweet little old Mrs. Bombarro--is in jail for murdering her husband with a fireworks rocket. Lexy knows the cops have got it wrong; all she needs is a few days to prove it and somewhere cheap to sleep at night. But checking into the Last Ditch Motel brings an unexpected slice of life and a whole world of trouble.